Reformulasi Metode Analisis Dakwah Digital: Integrasi SWOT–Iceberg sebagai Solusi atas Stagnasi Pendekatan Ilmiah dalam Studi Dakwah Kontemporer - Khaiza Lois Himmatul Ulya; Fira Maghfiroh; Amelia Rosanti; Ali Hasan Siswanto (Jurnal Budi Pekerti Agama Islam, 2025)
The development of digital da'wah demands a more in-depth, comprehensive, and data-driven methodological approach. However, contemporary da'wah research is still dominated by descriptive analysis that stops at mapping surface phenomena without exploring the underlying causal factors that determine the long-term effectiveness of da'wah. This weakness is increasingly apparent in the use of SWOT analysis, which has been widely applied in da'wah studies, but tends to be limited to producing categorization tables without an operational epistemic basis. Meanwhile, the era of digital da'wah presents a new, complex reality, where da'wah success is influenced not only by surface interactions such as the number of viewers, impressions, or follower growth, but also by latent factors such as audience cognitive motivation, platform algorithms, digital cultural context, identity construction, and societal value systems. This study aims to formulate a new methodological model through the integration of SWOT and the Iceberg approach to address this methodological stagnation. The research was conducted using qualitative methods based on literature analysis, comparative studies of strategic analysis models, and the construction of a conceptual model. The results show that the SWOT-Iceberg integration is able to produce a more multidimensional framework for digital da'wah analysis: SWOT diagnoses surface symptoms, while Iceberg explores patterns, causal structures, and mental models that shape phenomena. This combined model enables the development of more accurate, adaptive, and evidence-based da'wah strategies. It is concluded that the SWOT–Iceberg integration significantly contributes to the development of modern da'wah methodology by encouraging a shift from descriptive research to transformative diagnostic analysis, while simultaneously strengthening the scientific character of da'wah as an academic discipline based on a critical and measurable knowledge system.